2019
DOI: 10.3390/ijms20051035
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of IL-10 in Circulating Bregs and Inverted IL-10/TNF-α Ratio in Tears of Patients with Perennial Allergic Conjunctivitis: A Preliminary Study

Abstract: Allergic conjunctivitis (AC) is one of the most common ophthalmological disorders seen in clinical practice. Growing evidence from recent years suggests that a subset of IL-10-expressing B cells is involved in inflammatory allergic diseases. In this study, we aimed to evaluate the potential involvement of blood Bregs cells in perennial allergic conjunctivitis (PAC), and interleukins (IL)-1β, IL-6, IL-8, IL-10, and IL-12, and tumor necrosis factor (TNF)-α, were measured in tear samples and compared with healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…TNF-α monoclonal antibody significantly improves nasal symptoms in AR mice ( 20 , p. 517–523). Patients with allergic conjunctivitis demonstrate an immunological dysregulation, characterized by the low expression of IL-10 and an inverted tear IL-10/TNF-α ratio ( 21 ). A systematic review concluded that TNF-α and IL-6 may influence the risk of asthma ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α monoclonal antibody significantly improves nasal symptoms in AR mice ( 20 , p. 517–523). Patients with allergic conjunctivitis demonstrate an immunological dysregulation, characterized by the low expression of IL-10 and an inverted tear IL-10/TNF-α ratio ( 21 ). A systematic review concluded that TNF-α and IL-6 may influence the risk of asthma ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ophthalmological investigation was systematically documented by biomicroscopy, according to [ 39 ]. Schirmer test was performed without instillation of topical anesthetic, folding a Schirmer paper strip (AMCON Tear Flow Test Strips Nomax, Inc, MO, USA) over the temporal one-third of the lower lid margin inserted in the conjunctival sac for 5 min to measure the production of tears in millimeters.…”
Section: Methodsmentioning
confidence: 99%